Oral History Program Interview: Oscar Ervin (Irving) Kludt -Scotty - Kludt, Oscar Ervin
Born in 1923 in Alpena, Jerauld County, South Dakota, Kludt provides a non-"Okie," migrant perspective. He came to Lodi, California in March of 1935. In this interview, Kludt's gives his thoughts on the similarities between The Grapes of Wrath and Brentwood labor camps, the definition of "Okies" in comparison to South Dakotan migrants' treatment, existing economic prejudices, life as a fruit tramp, the WPA and crop/stock destruction, private and government camps, and organizing and strikes in the fields.